PENGAWASAN ANGKUTAN PENUMPANG UMUM KOTA LHOKSEUMAWE - Ana Zahara; Dicky Armanda (Sekolah Tinggi Ilmu Administrasi Nasional, 2022)
This study focuses on the supervision of public passenger transportation in Lhokseumawe City, the compliance of public passenger transportation, and the consistency of supervision. The research approach is a qualitative research approach with a descriptive-analytical research type. The data is analyzed using qualitative analysis, and the data collection techniques are interviews, observations, and documentation. The results showed although supervision has been carried out so far by conducting patrols twice daily to monitor the vicinity of the Malacca Strait intersection, the Department of Transportation for Tourism and Culture (Dishubparbud) of Lhokseumawe City has not controlled transportation that drops off and picks up passengers at the Malacca Strait intersection. As long as there is no follow-up or fines following the 2009 Law, i.e., anyone who drives a public motorized vehicle on a route that does not stop at the bus stop as referred to in Article 36 shall be punished with imprisonment for a maximum of 1 (one) month or a fine. There is a maximum of Rp. 250,000.00 (two hundred and fifty thousand rupiahs) from Dishubparbud, so many transportation drivers are still looking for Malacca Strait passengers. The actions taken so far are fines for other mistakes, such as crossing a red light and being caught not wearing a seat belt, as for the number of transportations. Those who were ticketed in 2013 were 41 vehicles, consisting of vehicles that did not have SIM, STNK, STUK, and KPS completeness.